Ciz1 cooperates with cyclin-A-CDK2 to activate mammalian DNA replication in vitro - Copeland, Nikki A; Sercombe, Heather E; Ainscough, Justin F.X; Coverley, Dawn (Journal of cell science, 2010)
Initiation of mammalian DNA replication can be reconstituted from isolated G1-phase nuclei and cell extracts, supplemented with cyclin-dependent protein kinases (CDKs). Under these conditions, cyclin E supports pre-replication complex assembly, whereas cyclin-A-associated kinase acts later to terminate assembly and activate DNA replication. The mechanism by which these events are coordinated is unknown. Here, we show that the replication factor Ciz1 interacts with cyclins E and A sequentially through distinct cyclin-binding motifs. Cyclin A displaces cyclin E from Ciz1 in a manner that is dependent on functional domains that are essential for its role in DNA replication. Furthermore, in cell-free assays, recombinant cyclin-A-CDK2 complexes and recombinant Ciz1 cooperate to promote initiation of DNA replication in late G1-phase nuclei. In addition, Ciz1 supports immobilization of cyclin A in isolated nuclei and depletion of Ciz1 by RNAi impairs immobilization, suggesting that Ciz1 promotes initiation by helping to target the kinase to a specific subnuclear compartment. We propose that Ciz1 acts to coordinate the functions of cyclins E and A in the nucleus, by delivering cyclin-A-associated kinase to sites that are specified by cyclin E, helping to ensure that they execute their functions in the same place and in the correct order.